2003
DOI: 10.1890/0012-9658(2003)084[1140:psaeda]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Prey State and Experimental Design Affect Relative Size of Trait- And Density-Mediated Indirect Effects

Abstract: Indirect effects, in which one species affects another through an intermediate species, can occur by changes in either the density or the traits of the intermediate species.Ecologists have focused primarily on density-mediated indirect effects, but have become interested in quantifying the relative sizes of trait-and density-mediated indirect effects. We examined how state-dependent prey behavior and experimental protocols affect the sizes of measured trait-and density-mediated indirect effects in a three-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
159
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(174 citation statements)
references
References 47 publications
10
159
0
5
Order By: Relevance
“…For example, Swifts Apus apus probably escape nocturnal predation entirely by roosting on the wing (Lack 1956;Backman and Alerstam 2001), and Dunlins Calidris alpina may spend several hours aloft to avoid predation by Peregrines Falco peregrinus at high tide (Dekker 1998). In general, if resources are abundant so that the costs of anti-predation behaviour can be met then predation risk is unlikely to manifest itself in terms of prey being directly killed by predators (Luttbeg et al 2003;Bolnick and Preisser 2005;Preisser et al 2009). …”
Section: Non-lethal Effects and The Subtle Population Effects Of Predmentioning
confidence: 99%
“…For example, Swifts Apus apus probably escape nocturnal predation entirely by roosting on the wing (Lack 1956;Backman and Alerstam 2001), and Dunlins Calidris alpina may spend several hours aloft to avoid predation by Peregrines Falco peregrinus at high tide (Dekker 1998). In general, if resources are abundant so that the costs of anti-predation behaviour can be met then predation risk is unlikely to manifest itself in terms of prey being directly killed by predators (Luttbeg et al 2003;Bolnick and Preisser 2005;Preisser et al 2009). …”
Section: Non-lethal Effects and The Subtle Population Effects Of Predmentioning
confidence: 99%
“…Although still rare relative to the hundreds of studies that have demonstrated the strong influence of adaptive phenotypic plasticity in ecosystems (reviewed by Werner and Peacor 2003, Miner et al 2005, Ohgushi 2005), a handful of studies have demonstrated how environmental factors such as resource availability (Luttbeg et al 2003, Hawlena et al 2011, ecosystem productivity (Turner 2004, Werner andPeacor 2006), and landscape features (e.g., water depth, tidal flows, habitat complexity, canopy cover; Rothley and Dutton 2006, Heithaus et al 2009) can strongly influence nonconsumptive effects and TMIEs by altering the trade-offs associated with adaptive phenotypic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, by conducting many replicate feeding and behavioral trials in the laboratory, we gained interesting insights regarding individual variation in predator−prey responses that warrant further attention. Our study adds to the growing body of empirical evidence supporting model predictions that individual variation in prey state alters TMII strength (Ovadia & Schmitz 2002, Luttbeg et al 2003, Persson & De Roos 2003, Kotler et al 2004, Freeman 2006, Rudolf 2012, Matassa & Trussell 2014, Gravem & Morgan 2016. …”
Section: Discussionmentioning
confidence: 53%
“…More recently, investigators have begun focusing on the context-dependency of TMII and factors altering its strength, such as environmental variation, features of informational cues, timing of measurements and individual variation in the traits of mediating species (Luttbeg et al 2003, Luttbeg & Trussell 2013, Matassa & Trussell 2014, Weissburg et al 2014, Gravem & Morgan 2016. For example, the transmission of predator cues to prey is strongly influenced by the environment, and air and water flow are particularly important for chemosensory cues (Smee et al 2010, Weissburg et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation